Pendampingan Pada Pengelolaan Sampah Menjadi Berkah Menuju Lingkungan Bersih, Sehat, dan Asri Di Desa Brumbu - Siti Fahimah (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2019)
Garbage is a problem that is as small but also crucial in society, it is seen as insignificant because only waste is not important, but it becomes crucial if it can cause negative impacts such as careless disposal at times, sewers or riverbanks cause flooding, dumped on the road causing buildup. Therefore, in handling waste, it must be done wisely. In the village of Brumbun, it is considered as a community that is aware of cleanliness, so they need an assistance to localize waste, so that programs are carried out with echoes from "garbage to be a blessing". Before conducting assistance, we found a buildup of garbage that was considered by the community as a problem that needed immediate treatment. The accumulated rubbish causes the drainage flow and the village river to lose its function, waste management is carried out by empowering the community in the hope of increasing community awareness of their environment. The advisors forididakakukeng have been working to form a waste management group and the implementation of waste management extension activities for the people of Brumbun village. Group formation is carried out by forming an arrangement of active administrators who will work in managing waste. After that, guidance was provided for them to support the planned programs, while the extension activities were carried out by bringing in an expert in the field of waste management named Mr. Rasmian, S.Pd. and the team from Hi Green Surabaya who will be a resource person in the field of waste management is a blessing.